Rhinoplasty: Experience in Combined Military Hospital, Dhaka - Ahmed, Md Bashir; Akter, Rehena; Ahmed, Salahuddin (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Rhinoplasty, perhaps is the most complex and challenging cosmetic surgical procedure performed today. Hence, a thorough preoperative evaluation and the surgical skill in performing the operation is most important for final desired outcome. Establishing an accurate diagnosis through a comprehensive nasal analysis is obligatory. Objective: To assess post-operative functional and aesthetic outcome and patient’s satisfaction of all rhinoplasty operations. Methods: Retrospective study carried out in combined military hospital, Dhaka. 50 patients with external nasal deformity who were operated for functional, aesthetic or for both reason were included. Patients’ satisfaction levels from the procedures were routinely documented in the post op visits as completely satisfied, partialy satisfied and not satisfied at all. Results: A total of 50 cases underwent rhinoplasty and septorhinoplasty operations. The most common reason of disfigurement was traumatic injury during games (40%). Different surgical procedures were done without any major complications. Except few most of the patients were fully satisfied. Conclusion: For better satisfaction of patients, adequate preoperative counseling and realistic expectations are warranted. Skillful surgical techniques reduce the chances of complications. Bangladesh J Otorhinolaryngol; April 2019; 25(1): 3-9